Analysis of the Use of Sistem Kelola Pembelajaran Based on the Technology Acceptance Model Approach - Febrito David Christian; Grace T. Pontoh; Hermita Arif (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research aims to determine the influence of self-efficacy, compatibility, and TAM on the acceptance of SIKOLA among students of the Faculty of Economics and Business at Hasanuddin University. Primary data obtained through a questionnaire with 363 respondents were analyzed with structured equation modeling analysis using IBM SPSS Statistics AMOS 23 software. Results showed that compatibility and ease of use significantly influenced usefulness. Self-efficacy did not affect usefulness, while self-efficacy and compatibility significantly influenced ease of use. Usefulness had a significant effect on actual usage, while ease of use did not impact actual usage. This research highlights that self-efficacy and compatibility are external factors suitable for examining the level of acceptance of the learning management system among users